Population Aging and Economic Growth: From Demographic Dividend to Demographic Drag? - Rainer Kotschy; David E. Bloom (Center for Economic Studies and ifo Institute (CESifo), 2023)
This paper examines the extent to which changes in working-age shares associated with population aging might slow economic growth in upcoming years. We first analyze the economic effects of changing working-age shares in a standard empirical growth model using country panel data from 1950–2015. We then juxtapose the estimates with predicted shifts in population age structure to project economic growth in 2020–2050. Our results indicate that population aging will slow economic growth throughout much of the world. Expansions of labor supply due to improvements in functional capacity among older people can cushion much of this demographic drag.
Keywords: J11; O11; O47; 330; population health; life expectancy; prospective aging; labor supply; economic development